Fuzzy Logic Tool for Getting Accurate Solutions - Dadios, Elmer P. (IntechOpen, 2015)
This book is a collection of chapters, concerning the developments within the Fuzzy Logic field of study. The book includes scholarly contributions by various authors pertinent to Fuzzy Logic. Each contribution comes as a separate chapter complete in itself but directly related to the books topics and objectives. The target audience comprises scholars and specialists in the field.